Uso do território e implantação de infraestruturas de transportes terrestres na Região Centro-Oeste através de Convênios Federais - Gallo, Fabricio (Geografares, 2011)
O texto objetiva analisar uma das facetas do território brasileiro: a celebração de Convênios entre o Ministério dos Transportes e os municípios da Região Centro-Oeste. Com a nova organização tributária proposta na Constituição de 1988, ocorreu uma forte descentralização das receitas o que proporcionou o crescimento considerável da participação dos municípios nas receitas disponíveis. O sistema de transferências intergovernamentais de recursos é de suma relevância para o planejamento territorial orquestrado pelas municipalidades. Use of territory and implantation of land transports infrastructure in Brazilian Center-West through Federal Covenants Abstract The text aims to analyze the voluntary transfers of resources from the Federal Government to the municipalities, through Covenants signed between the Department of Transportation and the municipalities of the Brazilian Center-West. These Covenants act as a mechanism that can be configured in promoter of new selectivity and hierarchies between places. Our analysis intends to identify how the Brazilian government makes use of constitutional mechanisms to implement and improve the territorial infrastructure, than among other things, provide greater fluidity for the agribusiness of Brazilian Center-west enabling the corporate use of Brazilian territory. DOI: 10.7147/GEO9.1389